DESIGN OF BORED PILE FOUNDATION AND DIAPHRAGM WALL WITH STRUT REINFORCEMENT IN HYBRID WORK BASED OFFICE IN CIBUBUR - Christina Suradji, Agnes
Cisco Indonesia HQ office has three similar buildings, each building consists two floors. The first building has one basement floor that functions as a parking area for office workers. This final project aims to calculate and design a foundation that can bear existing forces and a retaining wall for basement construction. The foundation analysis and design are assisted by GROUP and LPILE software to check the forces that occur on the foundation. The foundation used consists of one type of foundation - bored piles with 0.6 meters diameter which are arranged on a pile cap. One type of pile group configuration is used for the design - two bored piles in one pile cap. In the first building, the length of the bored pile foundation is 8 meters, starting at an elevation of -4,4 meters below the basement, and for the second and third buildings, the length is 11 meters, starting at an elevation of 0 meters. The retaining wall design analysis is assisted with PLAXIS 2D software to calculate the safety factor and lateral deflection that occurs in retaining walls with staged construction modeling. The chosen type of retaining wall is a diaphragm wall with 0.8 meters thickness and a total height of 15 meters. To withstand the existing lateral force, strut reinforcement is used at an elevation of -1 meter.